Attendance of general practitioners at child protection case conferences. Issue 6789 (8th June 1991) - Lea-Cox, C; Hall, A
Abstract : OBJECTIVE--To investigate general practitioners' attendance at and views on child protection conferences and their confidence in dealing with sexual abuse in children. DESIGN--Anonymous postal questionnaire sent to all general practitioners in Tower Hamlets and review of consecutive case conferences held by social services for three months in 1989. SETTING--Tower Hamlets health district. SUBJECTS--91 general practitioners, 56 of whom (62%) responded. MAIN OUTCOME MEASURES--Number of conferences attended, reasons for non-attendance, and reported confidence in dealing with sexual abuse. RESULTS--General practitioners estimated that 202 child protection conferences had been held in 1989 on their patients and that they had attended 85 of these. Information from social services for three months suggested that general practitioners had attended only nine of the 114 conferences reviewed. Timing of the conference was the most important reason for non-attendance. All respondents wanted access to the minutes of these conferences irrespective of their own attendance. Most general practitioners were very or moderately confident of their ability to detect child sexual abuse and non-accidental injury and to communicate with the family. CONCLUSION--More effort should be made to ensure that general practitioners are notified of case conferences and that the timing and location of conferences is compatible with their other commitments.